Analisis Kecepatan dan Kehandalan Pelayanan Jasa Perawatan dan Perbaikan terhadap Tingkat Kepuasan Pelayanan Unit Penunjang Akademik Perawatan dan Perbaikan Politeknik Negeri Bali - Ni Putu Diah Pratiwi; Ida Bagus Sanjaya; Gede Pradiva Adiningrat (Syntax Corporation Indonesia, 2024)
This study aims to analyze the variables of speed and reliability of maintenance and repair services to the level of service satisfaction of the Maintenance and Repair Academic Support Unit of the Bali State Polytechnic. This study uses a quantitative method with a population of all UPA-PP service users who occupy positions as Head of Department, Secretary of Department, Department Administration, Head of Study Program, Head of Unit, Head of Center, Head of Workshop/Lab, Workshop/Lab Technician, Head of Section and Head of Sub-Division as many as 138 people. The research sample consisted of 103 UPA-PP users who were selected through probability sampling using proportionate stratified random sampling with the Slovin formula. Data were collected using a Likert Scale-based questionnaire and analyzed by multiple linear regression. The results of the study show that partially, the velocity variable (X1) has a positive and significant effect on the level of service satisfaction (Y) with a coefficient value of 0.317 and a t-value of 3.237 > t table 1.98397 with a value of Sig. 0.002 < 0.05. And partially, reliability (X2) has a positive and significant effect on the level of service satisfaction (Y) with a coefficient value of 0.776 and a t-value of 6.490 > t table 1.98397 with a Sig. value of 0.000 < 0.05. Meanwhile, simultaneously the variables of speed (X1) and reliability (X2) have a positive and significant effect on the level of service satisfaction (Y) of F calculated 58.567 > F table 3.09 with a value of Sig. 0.000 < 0.05.